Implementasi Kurikulum Merdeka Belajar Kampus Merdeka (MBKM) dalam Pandangan Filsafat Pendidikan Pragmatisme - Achmad Busrotun Nufus; Kokom Komalasari; Dadang Sundawea; Suhartono Suhartono (Universitas Negeri Manado, 2022)
Merdeka Belajar Kampus Merdeka (MBKM) was created by the Ministry of Education and Culture with the aim that students are able to face various technological advances, social and cultural changes, as well as various challenges that exist in the world of business, work, and industry so that graduate students meet the criteria needed by the world. work, business and industry. This article analyzes the implementation and objectives of the MBKM curriculum from the point of view of pragmatism education philosophy. The method used in this research is the study of literature/library with the use of primary and secondary data references. The results show that the MBKM curriculum leads to the industrialization of graduates but the meaning and benefits of realizing rather than the expected value of learning the philosophy of education pragmatism has led graduates (students) to the path of success, productivity, and happiness, by accepting academic graduates in the world of work, business, and industry